Performance Analysis of Downlink Polarized Distributed Antenna Systems With Antenna Selection Diversity - Jungsun Um; Jaehyun Park (IEEE Access, 2024)
In this paper, we consider a distributed antenna system (DAS) with polarized antennas for the industrial internet-of-things, where distributed sensor nodes (SNs) with a single antenna are served by the closest distributed antenna (DA) port having multiple antennas. By using stochastic geometry, the interference in the polarized DAS is analyzed and the channel outage probability (OP) of the polarized DAS is also derived in a closed form. From the analytic results, the optimal vertically/horizontally polarized node densities are derived to minimize the channel OP. Furthermore, by investigating the effects of node density and polarization on the channel OP, we also develop a dual-polarized DAS, in which the effective density of co-polarized DA ports is the same with the density of all DA ports and, simultaneously, the interference from the active cross-polarized DA ports is effectively mitigated. By analyzing the channel OP for the dual-polarized DAS, the optimal node densities to minimize the overall channel OP and the effect of network design parameters on the channel OP is also investigated, which gives us a useful insight into the design of the polarized DAS.